WOMEN’S OF THE TANG DYNASTY APPAREL ELEMENT IN MODERN FULL DRESS DESIGN UTILIZATION - Yiqi, Lin; Seo, Miyoung; Khiaomang, Kriangsak (Fine Arts Journal: Srinakharinwirot University, 2025)
Background and Objectives: This study focuses on exploring the lifestyle patterns of people in the modern era, particularly the integration of contemporary fashion with visual art expressions and international design techniques. It also investigates innovations and lessons from both ancient and modern times. The primary objective is to examine the cultural elements of Han women’s clothing during the Tang Dynasty, including garments, accessories, and makeup. The study emphasizes the analysis of clothing structure, embroidery techniques, and color usage. Methods: The research involves the collection, organization, and analysis of historical documents from the Tang Dynasty in China. It also includes surveys and studies aimed at preserving the cultural components of Tang Dynasty fashion as a foundation for creative design. Data were gathered from digital museum resources, questionnaires, and interviews with industry experts. The findings led to the development of a fashion collection that interprets historical and cultural heritage through a modern perspective. Key Findings: The study provided a profound understanding of cultural content and design inspiration, enabling the integration of Tang Dynasty fashion elements into contemporary design concepts. It also fostered an appreciation of New Chinese Aesthetics, deepened the understanding of traditional Han culture, and contributed to the dissemination and creative reinterpretation of the artistic and cultural value of Hanfu in a modern context. Implications of the Study: Cultural elements should be selected with consideration of diverse materials and techniques to foster innovation. It is essential to grasp the "essence" of culture through its "external manifestations" in order to deeply understand traditional cultural values before applying them appropriately. Moreover, recognizing both the strengths and limitations of traditional attire and adapting it to meet the needs of modern consumers is crucial. The essence of design ultimately lies in responding to human needs and ways of living. Conclusions and Future Study: To ensure that research is efficient and beneficial in the long term, it should be free from bias and maintain academic neutrality toward national culture. Respect for traditional cultural foundations and in-depth exploration of historical contexts are vital. The study should also remain open to new ideas that encourage creativity, using contemporary design language as a tool to communicate traditional cultural values. Modern techniques and processes should be employed to interpret and adapt cultural heritage to fit present-day contexts.